Grounded - Brant, George, 1969- (Oberon modern plays., 2013)
Seamlessly blending the personal and the political, Grounded follows an F16 fighter pilot whose unexpected pregnancy ends her career in the sky. Repurposed to flying remote-controlled drones in Afghanistan from an air-conditioned trailer near Vegas, the Pilot struggles through twelve-hour work days hunting terrorists while tending to her family at night. Grounded will enjoy a 2013-14 rolling world premiere from the National New Play Network.